Rabbi Joseph Dov Soloveitchik on the experience of prayer - Schwartz, Dov (Emunot., 2019)
Through a careful reading of R. Soloveitchik's texts dealing with this topic, the book follows the consciousness of prayer across its various stages until maturity, starting with an analysis of Worship of the Heart, through to Reflections on the Amidah and other writings.